Aktivitas Antibakteri dan Skrining Fitokimia Ekstrak Etanol Daun Jambu Mete Anacardium occidentale L. Terhadap Pertumbuhan Escherichia coli Antibacterial Activity and Phytochemical Screening of Ethanol Extract of Cashew Leaves Anacardium occidentale L. Against Escherichia coli - Eka Astuty (MEDULA (JURNAL ILMIAH FAKULTAS KEDOKTERAN UNIVERSITAS HALU OLEO), 2022)
ABSTRACTBackground: All parts of the cashew tree Anacardium occidentale L. (especially the leaves and bark) have been widely used as traditional herbal medicines, and are used throughout the world. Thus, in recent decades, the traditional medicinal properties of the Anacardium plant, and its various biological effects are being studied extensively. Purpose(s): This study aims to conduct a preliminary study of the antibacterial properties and phytochemical screening of the ethanol extract of cashew leaves. Methods: The antibacterial test of was determined by the Kirby baeur disc paper diffusion method. Qualitative test of phytochemical content was carried out using chemical reagents. Results: The results indicated that the ethanol extract of cashew leaves has an inhibitory effect on the growth of Escherichia coli. The smallest inhibition zone was found in the extract with a concentration of 10% of 5.75 mm and the largest was found at a concentration of 100% with a diameter of 14 mm. The phytochemical screening revealed that extracts contained; alkaloids, flavonoids, steroids, terpenoids, phenolics, saponins, and tanins Conclusion: The ethanol extract of cashew leaves was able to inhibit the growth of Escherichia coli test bacteria at all concentration variations. Phytochemical screening also found that the ethanol extract of cashew leaves contains alkaloids, flavonoids, steroid terpenoids, phenolics, saponins, and tannins which are known to have antibacterial properties.Keywords: cashew, ethanol extract, antibacteria ABSTRAKLatar Belakang: Semua bagian pohon jambu mete Anacardium occidentale L. (terutama daun dan kulit batang) telah banyak digunakan sebagai obat herbal tradisional, dan digunakan di seluruh dunia. Dengan demikian, dalam beberapa dekade terakhir, sifat obat tradisional tanaman Anacardium, dan berbagai efek biologis sedang dipelajari secara ekstensif Tujuan: Penelitian ini bertujuan untuk melakukan studi pendahuluan sifat antibakteri dan skrining fitokimia dari ekstrak etanol daun jambu mete. Metode: Uji antibakteri ekstrak ditentukan dengan metode difusi kertas cakram Kirby baeur. Uji kualitatif kandungan fitokimia dalam ekstrak dilakukan dengan pereaksi kimia. Hasil: Ekstrak etanol daun jambu mete memiliki daya hambat terhadap pertumbuhan Escherichia coli. Zona hambat terkecil terdapat pada ekstrak dengan konsentrasi 10% sebesar 5,75 mm dan terbesar terdapat pada konsentrasi 100% dengan diameter 14 mm. Hasil skrining fitokimia menunjukkan bahwa ekstrak etanol daun jambu mete mengandung senyawa golongan alkaloid, flavonoid, steroid, terpenoid, fenolik, saponin, dan tanin Simpulan: Ekstrak etanol daun jambu mete mampu menghambat pertumbuhan bakteri uji Escherichia coli pada semua variasi konsentrasi. Skrining fitokimia juga menemukan bahwa dalam ekstrak etanol daun jambu mete mengandung alkaloid, flavonoid, steroid terpenoid, fenolik, saponin, dan tannin yang diketahui memiki kemampuan sebagai antibakteriKata Kunci: jambu mete, ekstrak etanol, antibakteri